EVALUATING IMAGE SEGMENTATION TECHNIQUES: A COMPARATIVE APPROACH - K.V, Shaheena; Dhanalakshmi S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Image segmentation plays a crucial role in image analysis, computer vision, and pattern recognition. It involves partitioning an image into meaningful regions to facilitate further analysis. Various segmentation techniques exist, including threshold-based methods, edge detection algorithms, region-based approaches, clustering techniques, and deep learning-based segmentation. This paper presents an overview of different segmentation methods, their comparative analysis, and practical implementation in Python.